2021
DOI: 10.35188/unu-wider/2021/100-6
|View full text |Cite
|
Sign up to set email alerts
|

The informal sector and the safety of female traders in Tanzania: A reflection of practices, policies, and legislation

Abstract: UNU-WIDER employs a fair use policy for reasonable reproduction of UNU-WIDER copyrighted content-such as the reproduction of a table or a figure, and/or text not exceeding 400 words-with due acknowledgement of the original source, without requiring explicit permission from the copyright holder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These measures have resulted in a proliferation of women-owned informal sector “micro-enterprises” with only one employee (see DTDA, 2021). Additionally, qualitative evidence shows that women benefiting from micro-loan schemes still hope to access larger, low-interest loans from the official banking sector, as well as business education and services (Chopra and Zambelli, 2017; Lindvert, 2017; Pallangyo, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These measures have resulted in a proliferation of women-owned informal sector “micro-enterprises” with only one employee (see DTDA, 2021). Additionally, qualitative evidence shows that women benefiting from micro-loan schemes still hope to access larger, low-interest loans from the official banking sector, as well as business education and services (Chopra and Zambelli, 2017; Lindvert, 2017; Pallangyo, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…schemes still hope to access larger, low-interest loans and business education (Chopra and Zambelli 2017;Lindvert 2017). It has also been reported that female traders face limited access to business development services in Tanzania (Pallangyo 2021). Furthermore, Berge et al (2015) show, using a randomized controlled trial, that women receiving such services benefit less from business training than men.…”
Section: Promoting Women's Self-employment Through Enterprise Creatio...mentioning
confidence: 94%
“…(Holmes and Jones 2013). A recent study from Tanzania highlights the challenges Tanzanian female traders face in accessing trading spaces, finance, and business development services (Pallangyo 2021). The particular vulnerability of women in the event of external shocks has been evidenced in the context of the COVID-19 pandemic.…”
Section: Social Protection: Gender Perspectives and Challenges In The...mentioning
confidence: 99%